Detection of OqxAB Efflux Pumps, a Multidrug-Resistant Agent in Bacterial Infection in Patients Referring to Teaching Hospitals in Ahvaz, Southwest of Iran - Mojtaba Moosavian; Mahtab Khoshkholgh Sima; Nazanin Ahmad Khosravi; Effat Abbasi Montazeri (International Journal of Microbiology)
Antibiotic resistance mechanisms in Enterobacteriaceae are causative agents of global health problems. Bacterial infections due to multidrug resistance (MDR) may be mediated by the overexpression of efflux pumps. In this study, we investigated the prevalence of oqxA and oqxB genes as two encoding agents of efflux pumps and the determination of antibiotic resistance rate in clinical isolates of Enterobacteriaceae. In this study, 100 Enterobacteriaceae isolates collected from different clinical specimens of infectious patients, such as wounds, urine, blood, discharge, and abscesses except stool, were examined. Identification of the isolates was performed using standard biochemical tests such as TSI, citrate, urea, lysine, SIM, MR-VP, and gas production. The antimicrobial susceptibility test was carried out by the Kirby–Bauer disk diffusion method according to CLSI guidelines, and finally, the oqxA and oqxB genes were detected by the PCR method. Among 100 Enterobacteriaceae isolates, Escherichia coli and Enterobacter gergoviae were the most common isolates with 71% and 20%, respectively. Also, the lowest isolates belonged to Enterobacter cloacae (3%) and Klebsiella pneumoniae (1%). Out of 100 Enterobacteriaceae isolates, 37 isolates (37%) were positive for at least one of oqxA or oqxB genes, while both of these genes were detected among 12% of them. oqxAB genes were detected in 8 cases of 20 (40%) Enterobacter gergoviae and 4 cases of 71 (5.7%) E. coli isolates. The antimicrobial susceptibility test showed that all isolates (100%) were susceptible to imipenem, while the maximum resistance to piperacillin, ceftriaxone, and cefotaxime were 69%, 55%, and 55%, respectively. Also, the results of this study showed that antibiotic resistance in Enterobacteriaceae isolates caused by oqxAB genes is increasing among patients in Iran. Therefore, identification of resistant isolates and antibiotic monitoring programs are essential to prevent the spread of MDR isolates.